Determınatıon of quality of life and medication adherence in patients with acute coronary syndrome - RABUŞ, ŞULE; TEZCAN, SONGÜL (My University, 2022)
Aim: Patients may have poor medication adherence after acute coronary syndromes (ACS). Most patients are treated for long periods of time with a combination of drugs for treatment or prophylaxis. Psychosocial problems, anxiety and depression are common in these patients and can lead to a decrease in quality of life. The aim of our study is to determine the quality of life, and medication adherence in patients with ACS. Methods: This prospective and descriptive study was conducted at a cardiology clinic in Istanbul between May-October 2022. The patients hospitalized with ACS diagnosis were included in the study. Medication Adherence Report Scale (MARS) and the Turkish version of the Health-related Quality of Life-4 (CDC HRQOL-4) Scale were applied to patients only once. Results: The median age of the patients was 60 (53-70), the median number of diseases was 2 (0-4) and the median number of drug use was 3 (0-6). It was observed that the quality of life decreased with age (p<0.05). The quality of life of most of the female patients (over 70%) was found to be lower than male patients (p<0.05). At least one medicine was used in 70% of the patients, and the median score of MARS score was determined as 10 (0-14). It was determined that MARS scores were positively correlated with age and number of comorbid diseases and the number of drugs (p<0.05). Conclusions: In our study, it has been determined that age and female gender may negatively affect the quality of life of the patients. Although the number of comorbid diseases and the number of drugs were low in patients with ACS, it was observed that medication adherence was low. We think that clinical pharmacists can co
Keywords: Acute coronary syndrome; quality of life; medication adherence; hospital setting